Photovoltaic Energy Conversion System Constructed by High Step-Up Converter with Hybrid Maximum Power Point Tracking - K. I. Hwu; W. C. Tu; C. R. Wang (International Journal of Photoenergy)
A photovoltaic energy conversion system, constructed by high step-up converter with hybrid maximum power point tracking (HMPPT), is presented. A voltage converter with a high voltage conversion ratio is proposed, which is simple in circuit and easy in control. After this, such a converter operating with a suitable initial duty cycle of the pulsewidth-modulated (PWM) control signal, together with the proposed HMPPT algorithm combining the fractional open-circuit voltage method and the incremental conductance method, is applied to the photovoltaic energy conversion system. By doing so, not only the maximum power point tracking speed can be increased, but also the oscillation around the maximum power point can be reduced. Aside from these, the field programmable gate array (FPGA) is used as a control kernal of the overall system, so as to realize the HMPPT and fully digitalized control. Finally, via a PV simulator, some experimental results are provided to verify the effectiveness of the proposed photovoltaic energy conversion system.